Science by the People : Participation, Power, and the Politics of Environmental Knowledge - Kimura, Aya Hirata, 1974-; Kinchy, Abby J. (Book collections on Project MUSE., 2019)
"Citizen science," data collection and scientific research by people who do not have scientific credentials, is an increasingly popular activity, from bird counts to amateur water sample collection to air quality monitoring. Such efforts are at the heart of many of today's environmental and health controversies. As scholars in the interdisciplinary field of science and technology studies (STS), the authors ask readers to consider how citizen science enhances struggles for social change beyond merely generating data through volunteer participation, and they provide practical examples and scenarios to aid practitioners in planning strategic citizen science projects that align with their values. While there are a number of monographs detailing specific citizen science cases, there is no book that takes stock of multiple case studies to explore how citizen science may or may not address social inequality and produce accountability of government and corporate entities